Terrorism and homeland security : - Purpura, Philip P. (Butterworth-Heinemann, 2007)
The book explains practical issues, handled by senior government officials, first responders and private security practitioners. Theory from more than 20 disciplines provides a foundation for the book, including criminal justice, international relations, government, psychology, sociology, military science, business, structural engineering and public health.-Morning News, Florence, SC, January 21, 2007